Batas, Katarungan, at Kalikasan: Isang Kritikal na Pagmuni sa Ekolohiya at Lipunan - Batongbacal, Jay L. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 7 No 1 (2011))
This article is a commentary and critique of the concept of ‘environmental justice’ that lately has become much more prominent in discourses on the environment, especially in the debates and advocacy on climate change. After briefly considering the origins of the concept, it is argued that environmental justice is limited by its liberal democratic roots—it is an extension of a discourse that ultimately is based on atomism, centralization of power, and legitimization of the marginalization of groups from true democratic decision-making processes. This arises from the absence of a coherent philosophy and system of principles that can balance social demands for access and allocation of resources against individual proclivities toward unending appropriation and accumulation, preventing ‘environmental justice’ from addressing the counter-environmental effects of consumerism and displacement. To offer an alternative called ‘ecological social justice’, a reconsideration of the environment within Karl Polanyi’s definition of economy and critique of the market society is correlated with the definition of ‘social justice’ and the right to a healthy environment in Philippine jurisprudence.
Keywords: Social justice, environment, environmental justice, environmental ethics, Philippine jurisprudence, Karl Polanyi, ecological social justice, katarungang panlipunan, ekolohikal na katarungang panlipunan